Intrinsically Flame‐Retardant Polyamide 6 by Anionic Ring‐Opening Copolymerization with a Phosphorous‐Containing Comonomer - Carlo Pani; Hagen J. Altmann; Patrick Probst; Iris Elser; Mark Steinmann; Simon König; Philipp Kreis; Lisa Kuske; Dominik Weidich; Anke Gähr; Jonas Groos; Julian Kappler; et al. (Macromolecular Materials and Engineering)
Abstract A three‐step synthetic route is established for the synthesis of a phosphorus‐containing ε‐caprolactam derivative, starting from cyclohex‐2‐enone and diphenylphosphinous chloride, followed by a Beckmann rearrangement. 2D NMR spectroscopy reveals that the phosphorus moiety is selectively localized at the 4‐position of the caprolactam ring. Different amounts of the phosphorus‐containing comonomer are systematically incorporated into polyamide 6 by anionic ring‐opening copolymerization with ε‐caprolactam at elevated temperatures. Polymerization reactions are initiated by a latent, CO2 protected N‐heterocyclic carbene in the presence of N‐acetyl caprolactam and MgCl2. The phosphorus content is determined by inductively‐coupled plasma‐optical emission spectroscopy (ICP‐OES) analysis. Limiting oxygen indices up to 23.5 are found for polymers containing ≈1 wt.‐% of phosphorus. The thermal properties of the copolymers are determined and compared to those of polyamide 6.